PENGARUH MODEL KOOPERATIF TIPE MAKE A MATCH TERHADAP HASIL BELAJAR IPAS KELAS IV SDN 77 PALEMBANG - Zaleha, Siti; Rahman, Andi; Lestari, Hikmah (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2025)
This study aims to determine the effect of the cooperative learning model Make A Match on the learning outcomes of fourth-grade students in the Natural and Social Sciences (IPAS) subject at SDN 77 Palembang. This research employed a quantitative experimental method with a True Experimental Design and a Posttest-Only Control Design approach. The population consisted of all fourth-grade students at SDN 77 Palembang, totaling 39 students divided into two classes: IVA and IVB. The sampling technique used was total sampling, involving both classes. The average score obtained by class IVA was 70, while class IVB achieved an average score of 85. The hypothesis testing was conducted using an independent sample t-test with the criterion that Ha is accepted if tcount>ttable. The results showed that tcount=3.912>ttable=1.687 and the significance value was p=0.000<0.05. Thus, the alternative hypothesis (Ha) was accepted and the null hypothesis (Ho) rejected, indicating that the Make A Match cooperative learning model significantly affects students’ IPAS learning outcomes at SDN 77 Palembang.